Opinions of an Old Contrarian - Friddell, Guy ([Place of publication not identified] The Pilot Press, 1997)
A selection from the author's columns which originally appeared in The Virginian-Pilot and the Richmond Times-Dispatch, over a 40 year period.
Magic of Christmas -- Young 'uns -- The Better Half -- No one said it'd be easy -- Un-conventional -- Jefferson and others -- Of maestros and minstrels -- On and off the field -- Ya Ol' Contrarian -- Making progress, confoundit -- Pop goes the culture -- In the public's eye -- The produce aisle -- War and peace -- The final frontier -- Fur and feathers -- Celebrations.